Pulsed-laser-ablated gold-nanoparticles saturable absorber for mode-locked erbium-doped fiber lasers - Noor Zirwatul Ahlam, Naharuddin; M. H., Abu Bakar; Sadrolhosseini, Amir Reza; N., Tamchek; Alresheedi, Mohammed Thamer; Abas, A. F.; Mohd Adzir, Mahdi (Elsevier Ltd, 2022)
We demonstrate the optical performance of passively mode-locked pulses in erbium-doped fiber laser incorporating gold-nanoparticles (Au-NPs) as a saturable absorber (SA). Au-NPs of diameters between 5 to 15 nm were synthesized using the pulsed laser ablation method and blended with polydimethylsiloxane polymer. The resulting nanocomposite was deposited on the tapered region of a microfiber with a spin-coating method. The proposed Au-NPs SA recorded a modulation depth of 0.4% and low saturation intensity of 0.1 MW/cm2 leading to stable mode-locking operation in the erbium-doped fiber laser cavity at a low threshold pump power of about 45.6 mW. A mode-locked pulse train with a duration of 933 fs, pulse repetition rate of 6.25 MHz, and peak-to-pedestal extinction ratio of 54.1 dB was achieved at a pump power of 168.1 mW. The obtained results demonstrate that the spherical Au-NPs synthesized by pulsed laser ablation is a feasible material for SA fabrication, validating its saturable absorption properties in a 1.55 μm wavelength region.